Photoredox-catalyzed sulfenylation/cyclization of N-aryl-N-tosylpropargylamine with disulfide: A concise route to 3-phenylthioquinoline. Issue 20 (17th May 2019) - Wang, Yu-Zhao; Zhang, Heng-Rui; Zhou, Li; Fang, Jun-Dan; Liu, Xue-Yuan
Abstract: A facile and novel protocol for one-pot synthesis of 3-phenylthioquinoline derivates via visible-light induced tandem cyclization of N -aryl- N -tosylpropargylamine with disulfides was developed. This unprecedented method, involving CS bond formation, detosylation and aromatization, afforded the desired products in a broad substrate scope under mild conditions. Graphical abstract: Image 1